Low-temperature combustion synthesis of Bi4Ti3O12 plate-like structure and some of its characteristics - Al-Amani, Umar (Universiti Putra Malaysia, 2010)
Bismuth titanate, Bi4Ti3O12 was prepared at different hydrolysis temperature and characterized with XRD, Rietveld analysis, TG-DTA, FESEM and TEM. The results indicated that the pure bismuth titanate was obtained after combustion at lower temperature of about 260oC. Interestingly, no calcination step involved to obtain bismuth-structured layered. The effect of hydrolysis temperature at 40, 50 and 60oC on phase formation, lattice parameter, crystallite size, thermal behavior as well as grain morphologies was investigated.